Drama, Poetry and Music in Late-Renaissance Italy The life and works of Leonora Bernardi - Cox, Virginia (UCL Press, 2023)
Leonora Bernardi (1559-1616), a gentlewoman of Lucca, was a highly regarded poet, dramatist and singer. She was active in the brilliant courts of Ferrara and Florence at a time when creative women enjoyed exceptional visibility in Italy. Like many such figures, she has since suffered historical neglect. Drama, Poetry and Music in Late-Renaissance Italy presents the first ever study of Bernardi's life, and modern edition of her recently discovered literary corpus, which mostly exists in manuscript. Her writings appear in the original Italian with new English translations, scholarly notes, critical essays and contributions by Eric Nicholson, Eugenio Refini and Davide Daolmi Based on new archival research, the substantial opening section reconstructs Bernardi's unusually colourful life. Bernardi's works reveal her connections with some of the most pioneering poets, dramatists and musicians of the day, including her mentor Angelo Grillo and the first opera librettist Ottavio Rinuccini. The second major section presents her pastoral tragicomedy Clorilli, one of the earliest secular dramatic works by a woman. It was apparently performed in the early 1590s at a Medici villa near Florence, before Grandduke Ferdinando I de' Medici, and his consort Christine of Lorraine, but now exists in an enigmatic Venetian manuscript. The third section presents Bernardi's secular and religious verse, which engaged with new trends in lyric and poetry for music, and was set by various key composers across Italy.